Communication at School – a Threat or an Opportunity for Students’ Communicative Competencies? Searching for Answers - Kuszak, Kinga (Kultura-Społeczeństwo-Edukacja, 2016)
The article tackles the issue of communication in school environment. The first part discusses communication as a dialogue between its participants, who shape its course together, taking turns and forming adjacency pairs. The author moves on to focus on the distinctive features of teacher-student communication. She lists and analyses its following traits: lack of students’ opportunity to contribute to the creation of the dialogue, a high level of formality, asymmetry of rights and privileges available to the participants of the communication process, prevalence of a monologue of meanings over a dialogue and negotiation of meanings. The article concludes with proposals for educational practice.